2015
DOI: 10.5713/ajas.15.0120
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Alkaline Phosphatase: Potential Roles in Promoting Gut Health in Weanling Piglets and Its Modulation by Feed Additives — A Review

Abstract: The intestinal environment plays a critical role in maintaining swine health. Many factors such as diet, microbiota, and host intestinal immune response influence the intestinal environment. Intestinal alkaline phosphatase (IAP) is an important apical brush border enzyme that is influenced by these factors. IAP dephosphorylates bacterial lipopolysaccharides (LPS), unmethylated cytosine-guanosine dinucleotides, and flagellin, reducing bacterial toxicity and consequently regulating toll-like receptors (TLRs) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 66 publications
0
19
1
Order By: Relevance
“…The intestinal environment plays a critical role in maintaining good health ( Farhadi et al, 2003 ; Melo et al, 2015 ). DAO is one of the indicators of intestinal epithelial integrity ( Tossou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal environment plays a critical role in maintaining good health ( Farhadi et al, 2003 ; Melo et al, 2015 ). DAO is one of the indicators of intestinal epithelial integrity ( Tossou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, piglets administrated with Ba had much lower DAO activity compared with antibiotic group, which may indicate much better state of intestinal integrity. AKPase is a new factor which contributes to maintain gut homeostasis ( Lalles, 2014 ; Melo et al, 2015 ). The deletion of intestinal AKPase gene caused a significant decrease of tight junction protein expression and function ( Liu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AKP is an enzyme capable of hydrolysing phosphate esters in an alkaline medium. The AKP is also involved in digestive‐absorptive processes of nutrients and the gut health by dephosphorylating bacterial lipopolysaccharides (LPS) and regulating Toll‐like receptors (TLR) activation immune in small intestine (Melo et al., ). Our results showed that IOF of Arg had a 1.5‐fold increase in duodenal AKP activity than other groups, suggesting that IOF of Arg contributed to improving the gut health and digestive‐absorptive function of small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the mechanisms of gut epithelial protection by IAP or iHSPs and their modulation by dietary components have been described, at least partly in the swine species too (e.g. for IAP: [47]).…”
Section: Introductionmentioning
confidence: 99%